2001
DOI: 10.1002/fedr.4921120506
|View full text |Cite
|
Sign up to set email alerts
|

Seedling morphology of some mangroves of sundarbans, India: A taxonomic approach: With 4 figures and one table

Abstract: Germination type and seedling morphology of 16 true mangrove species under ten families were studied. Seedlings were either raised in vitro or collected from natural habitat. True viviparous type of germination occurs in the members of Rhizophoraceae, cryptocotylar hypogeal in Excoecaria, Heritiera, Phoenix and Xylocarpus, phanerocotylar geal type in Aegiceras and Aegialitis, and phanerocotylar epigeal type in the rest of the taxa. Viviparous germination is considered to be the most complex phenomenon in evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…For sustainable establishment of young seedlings on inhospitable substrates (because of heavy rain flashes in sloppy terrain), germination of seeds occurs and the hypocotyl pierces the fruit wall before seed dispersal, which is unusual in land plants, except in some typical estuarine plant communities such as the mangroves, where it is very common. Seed germination is, therefore, more complex and shows reformed epigeal germination, which is considered to be a highly evolved process among the different types of germination (Das et al, ). Cota‐Sánchez and Abreu () postulated that among flowering plants viviparous germination is a rare occurrence; only 143 genera and 195 species spanning 80 vascular plant families show vivipary (less than 0.1% of the total number of angiosperms so far).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sustainable establishment of young seedlings on inhospitable substrates (because of heavy rain flashes in sloppy terrain), germination of seeds occurs and the hypocotyl pierces the fruit wall before seed dispersal, which is unusual in land plants, except in some typical estuarine plant communities such as the mangroves, where it is very common. Seed germination is, therefore, more complex and shows reformed epigeal germination, which is considered to be a highly evolved process among the different types of germination (Das et al, ). Cota‐Sánchez and Abreu () postulated that among flowering plants viviparous germination is a rare occurrence; only 143 genera and 195 species spanning 80 vascular plant families show vivipary (less than 0.1% of the total number of angiosperms so far).…”
Section: Resultsmentioning
confidence: 99%
“…True vivipary is considered to be a unique and advanced occurrence in the life cycle of some seed plants. The common occurrence of vivipary or modified vivipary (Cryptovivipary) can be noted in many mangrove taxa (Das, Ghose, & Paria, ). Callaghan and Emanuelsson () opined that vivipary is an adaptive feature of disturbed habitat and reported that about 20% of the vascular plant taxa show vivipary in the Karsa Glacier of the Swedish Lapland region.…”
Section: Introductionmentioning
confidence: 99%
“…The voucher specimens were deposited in Calcutta University Herbarium (CUH), India. For the method of the description of seedlings, several literatures [34,35,36,37,38,39,40] were followed. The reliable expressed as "reduced" (root 0.9-2.4 mm; hypocotyl 0.1-1.9 mm; epicotyl 0.1-1.5 mm), and "elongating" (root 2.5-6 mm; hypocotyl 2-5 mm; epicotyl 1.6-3 mm).…”
Section: Methodsmentioning
confidence: 99%
“…For method of description of seedlings, Vogel (l.c. ), Das et al (2001), Mukhopadhyay et al (2013), and Paria (2014) were followed. The critical observations on the hypocotyl, surface and venation pattern of paracotyledons, first leaf, and subsequent leaves were done with the help of binocular stereomicroscope (WILD HEERBRUGG M8).…”
Section: Methodsmentioning
confidence: 99%